LINEAR QUADRATIC CONTROL SYSTEM WITH INTEGRAL ACTION ON SPEED OF PERMANENT MAGNET SYNCHRONOUS MOTOR - Azizah, Fahira
The use of Permanent Magnet Synchronous Motor, or PMSM has increased rapidly in recent years, mainly in electric vehicles where it is used as the main drive motor due to its several advantages. In electric vehicle systems, one of the strategies to optimize the performance of electric cars is to design an efficient motor speed control. Designing an efficient motor speed control can affect a number of factors, such as the efficiency of converting electrical energy into motion, vehicle speed, and battery durability. Many ways are pursued for this energy efficiency, including through setting the optimal speed control of the motor in an electric vehicle. In this research, a PMSM motor speed control system with minimal control signal energy is made. The optimal control system scheme is made with a linear quadratic performance index, or Linear Quadratic Integrator (LQI). PI controller is used as a comparison. It is desirable that the created LQI controller satisfies the required response specifications. In realizing the torque control method, Field Oriented Control (FOC) is used in this paper. To validate the effectiveness of the proposed method, simulation and implementation have been performed using Texas Instrument's Motor Control Kit hardware model which consists of: Launchpad F28069M microcontroller, Boostxl 8305-evm motor driver, and Teknic 2310P dual-motor (PMSM) connected to Simulink Matlab. Experimental results have confirmed that the LQI technique can offer minimum control signal energy performance and satisfy the required response specifications.